Characteristics Of Automobile Terms - Sheralieva Shakhnoza Irkinovna (Zien Journals, 2022)
It seems to us that it is most logical to consider the vocabulary from the point of view of the transformations used to create an equivalent translation. It is especially important, in our opinion, that unusual, not the most obvious transformations are not left without attention
Keywords: single-word doublets; terminological phrases; basic concept; specialized terms and nomenclature units